PENGARUH KOMPOSISI MEDIA TANAM DAN PUPUK NPK MAJEMUK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA STADIA PRE NURSERY - Segara, Bayu; Hawalid,, Heniyati; Moelyahadi, Yopie (Universitas Muhammadiyah Palembang, 2015)
Effect of Media Composition Plant and Fertilizer NPK Compound on Growth in Stadia Seed Oil Palm Pre Nursery. This thesis aims to determine the effect of planting media composition and NPK compound fertilizer on the growth of seedlings of oil palm (Elaeis guineensis Jacq.) Stadia pre – nursery in polybag. This research has been conducted in the experimental field of Faculty of Agriculture, University of Muhammadiyah Palembang C Campus Hamlet I Semambu Island Village District of North Indralaya Ogan Ilir South Sumatra in April 2015 until July 2015. The method used was a randomized block design (RAK) are arranged in a factorial with 9 and 3 combined treatment group. The first treatment factors, namely composition Growing Media (M), M1 = PMK Soil, M2 = PMK Soil : Compost tankos (2: 1), M3 = PMK Soil: Compost tankos (1: 2). Both factors Granting NPK compound consisting of N1 = 5 g / polybag, N2 = 10 g / polybag, N3 = 15 g / polybag. Variables observed consisted of plant height (cm), number of leaves (pieces), the number of primary roots (pieces), primary root length (cm) and plant dry weight (g). Based on the results of analysis of variance showed that the composition of the planting medium to very real significant effect on plant height and length of the primary root, but the effect is not noticeable to all other variables, while treatment of compound NPK fertilizer significantly to very significantly on all the observed variables. Treatment interaction effect was not significant on all observed variables, but very significant effect on the primary root length.